PENGGUNAAN FITUR VIDGRAM PADA AKUN @YUFID.TV DI INSTAGRAM SEBAGAI TREN MEDIA DAKWAH - MANNAN, AUDAH; FACHRI, AKHMAD (Jurnal Dakwah Tabligh, 2019)
This research is a study that describes the use of Yufid Tv on Vidgram's feature as a trend of communication media. The research objective was to find out the use of vidgram features as a propaganda media trend by Yufid Tv, and to find out the da'wah material given by Yufid Tv on Instagram, as well as to find out the pros and cons of da'wah through Yufid Tv's vidgram feature on Instagram. The results of research conducted on the @ yufid.tv account on Instagram, found that Yufid Tv uses the vidgram feature to upload videos with the type of video poster. The use of the vidgram feature with the video poster model has become a media for propaganda to remain today with several factors, namely: the user's response to video posters, the existence of communities that expect da'wah through video posters, and crews focused on making videos. The da'wah material delivered by Yufid Tv on Instagram includes the material of aqidah, syariat, muamalah, and morality. The advantages of da'wah with the vidgram feature are ease of use of supporting features and tools, attractive interface display, and the impression of light and short content. The disadvantages of this feature are the metadata and content elements that cannot be adjusted like content on other social media, and there is no seekbar on the vidgram feature.